PET Imaging for Dynamically Monitoring Neuroinflammation in APP/PS1 Mouse Model Using [18F]DPA714 - Hu, Wei; Pan, Donghui; Wang, Yalin; Bao, Weiqi; Zuo, Chuantao; Guan, Yihui; Hua, Fengchun; Yang, Min; Zhao, Jun (Frontiers in Neuroscience, 2020)
Background: In the pathogenesis of Alzheimer's diseases, microglia plays an increasing important role. Especially, molecular imaging of neuroinflammatory targeting microglia activation and high expression of 18-kDa translocator protein is a hot research focus in recent years. Dynamically monitor neuroinflammation is crucial for discovering the best time point of antiinflammatory therapy. Motivated by this, PET imaging in a APP/PS1 mouse model of Alzheimer's Diseases using 18F-labeled DPA-714 to monitor microglia activation and neuroinflammation are performed in this paper.